Nanoemulsion: A Review on Mechanisms for the Transdermal Delivery of Hydrophobic and Hydrophilic Drugs - Dalia S. Shaker; Rania A. H. Ishak; Amira Ghoneim; Muaeid A. Elhuoni (MDPI AG, 2019)
Nanoemulsions (NEs) are colloidal dispersions of two immiscible liquids, oil and water, in which one is dispersed in the other with the aid of a surfactant/co-surfactant mixture, either forming oil-in-water (o/w) or water-in-oil (w/o) nanodroplets systems, with droplets 20−200 nm in size. NEs are easy to prepare and upscale, and they show high variability in their components. They have proven to be very viable, non-invasive, and cost-effective nanocarriers for the enhanced transdermal delivery of a wide range of active compounds that tend to metabolize heavily or suffer from undesirable side effects when taken orally. In addition, the anti-microbial and anti-viral properties of NE components, leading to preservative-free formulations, make NE a very attractive approach for transdermal drug delivery. This review focuses on how NEs mechanistically deliver both lipophilic and hydrophilic drugs through skin layers to reach the blood stream, exerting the desired therapeutic effect. It highlights the mechanisms and strategies executed to effectively deliver drugs, both with o/w and w/o NE types, through the transdermal way. However, the mechanisms reported in the literature are highly diverse, to the extent that a definite mechanism is not conclusive.